3 - Les Déterminants de la Consommation Urbaine à Ouagadougou - Thiombiano, Taladidia (Africa Development, 1988)
ABSTRACT: Why do African governments devote huge amounts of money to import rice or wheat? Why is the consumption of rice increasing and what strata of the population is the principal consumer of rice? The parameters which influence or determine food consumption are numerous and range from simple to complex considerations depending on the food items under discussion. Their degree of complexity also depends on whether the determinants are objective factors such as income, price or size of family or subjective ones such as taste and religion. In urban areas such as Ouagadougou, urbanization is an important variable in the choice of cereals. An empirical study on consumption patterns of households differentiated by strata and imported local cereals indicates that income is the determinant variable in the consumption of various food products. It was found that middle income households consume more local cereals whereas rich and poor households tend to consume more rice. However, in the case of poor households, it is not the price of rice which is the significant explanatory factor. The nature of urban employment and the time needed to prepare a given food item are important determinants. Processing and cooking local cereals is much more time consuming than the preparation of rice. Consequently, in urban areas, an increase in household income or a decrease in the price of traditional cereals will contribute, paradoxically, to in creasing the requirements for imported cereals and a decrease in the consumption of local cereals. If the government were to increase rice prices, low income households will be penalized. An appropriate food policy will have to be based on a critical examination of the various determinants of urban food consumption patterns.